Haemoplasmas in wild rodents: Routes of transmission and infection dynamics. Issue 18 (29th August 2018) - Cohen, Carmit; Shemesh, Merav; Garrido, Mario; Messika, Irit; Einav, Monica; Khokhlova, Irina; Tasker, Séverine; Hawlena, Hadas
Abstract: The way that some parasites and pathogens persist in the hostile environment of their host for long periods remains to be resolved. Here, longitudinal field surveys were combined with laboratory experiments to investigate the routes of transmission and infection dynamics of such a pathogen—a wild rodent haemotropic bacterium, specifically a Mycoplasma haemomuris ‐like bacterium. Fleaborne transmission, direct rodent‐to‐rodent transmission and vertical transmission from fleas or rodents to their offspring were experimentally quantified, and indications were found that the main route of bacterial transmission is direct, although its rate of successful transmission is low (~20%). The bacterium's temporal dynamics was then compared in the field to that observed under a controlled infection experiment in field‐infected and laboratory‐infected rodents, and indications were found, under all conditions, that the bacterium reached its peak infection level after 25–45 days and then decreased to low bacterial loads, which persist for the rodent's lifetime. These findings suggest that the bacterium relies on persistency with low bacterial loads for long‐term coexistence with its rodent host, having both conceptual and applied implications.